BORON-RICH MUD VOLCANOES OF THE BLACK SEA REGION: MODERN ANALOGUES TO ANCIENT SEA-FLOOR TOURMALINITES ASSOCIATED WITH SULLIVAN-TYPE PB-ZN DEPOSITS? - Slack J.F.; Turner R.J.W.; Ware P.L.G. (My University, 1998)
Large submarine mud volcanoes in the abyssal part of the Black Sea south of the Crimean Peninsula are similar in many respects to synsedimentary mud volcanoes in the Mesoproterozoic Belt-Purcell basin. One of the Belt-Purcell mud volcanoes directly underlies the giant Sullivan Pb-Zn-Ag deposit in southeastern British Columbia. Footwall rocks to the Sullivan deposit comprise variably tourmalinized siltstone, conglomerate, and related fragmental rock; local thin pyrrhotite-rich and spessartine-quartz beds are interpreted as Fe and Fe-Mn exhalites, respectively. Analogous Fe- and Mn-rich sediments occur near the abyssal Black Sea mud volcanoes. Massive pyrite crusts and associated carbonate chimneys discovered in relatively shallow waters (˜200 m depth) west of the Crimean Peninsula indicate an active sea-floor hydrothermal system. Subaerial mud volcanoes on the Kerch and Taman Peninsulas (˜100 km north of the abyssal mud volcanoes) contain saline thermal waters that locally have very high B contents (to 915 mg/L). These data suggest that tourmalinites might be forming in or near submarine Black Sea mud volcanoes, where potential may also exist for Sullivan-type Pb-Zn mineralization.
Keywords: Mesoproterozoic; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская